Methods of influencing the exchange rate: problems of currency regulation and ways to overcome them (Journal of Economic Research & Business Administration, 2020)
Currency regulation plays a significant role in the state economic policy. Depending on the goal,currency regulation can stimulate or constrain economic development in the country and, accordingly,affect the state of individual sectors, industries and enterprises, as well as the place of the state in theworld market. In modern conditions of economic globalization, the exchange rate is becoming one ofthe main integrated macroeconomic indicators, which affects not only the foreign economic activity ofthe state, but also, in general, the socio-economic development of our country. The imbalance of theforeign exchange market, the negative trade balance, high inflation rates indicate that the problem ofconducting an effective exchange rate policy and establishing the optimal level of the exchange rateremains unresolved. It is necessary to choose the optimal system for regulating the rate of currency quotationsto solve these problems. The paper discusses theoretical approaches to the system of regulationof exchange rate regimes. Systematized and classified methods of currency regulation. The proposedapplication of a systematic approach to the stabilization of the exchange rate, which promotes the integrity,hierarchy, structuring of currency systems. And this paper also discusses the problems of currencyregulation and ways to overcome them.